Institutional investors in the Czech voucher privatisation - Magdalena Šuterová (DANUBE: Law, Economics and Social Issues Review, 2020)
Voucher privatisation that proceeded in the Czech Republic in the 1990s was a realisation of a unique experiment which resulted in the transfer of almost half of state-owned enterprises to private hands within two years. A substantial part of these private hands was represented by intermediaries - the investment privatisation funds (IPFs). Their presence in the privatisation is often criticised as the cause of the extensive tunnelling. The aim of the paper is to find out how these funds performed after the privatisation. Using the standard Capital Asset Pricing Model, with OLS parameter estimations, I conclude that the so-called tunnelling was not as extensive, and that the privatisation funds were not as harmful for the privatisation as is believed.
Keywords: 330; Investment Privatisation Funds; Asset Stripping; Tunnelling; Voucher Privatisation